Differential Response to Cardiac Resynchronization Therapy and Clinical Outcomes According to QRS Morphology and QRS Duration - Dupont, Matthias; Rickard, John; Baranowski, Bryan; Varma, Niraj; Dresing, Thomas; Gabi, Alaa; Finucan, Michael; Mullens, Wilfried; Wilkoff, Bruce L.; Tang, W.H. Wilson (Journal of the American College of Cardiology, 2012)
The goal of this study was to examine the relative impact of QRS morphology and duration in echocardiographic responses to cardiac resynchronization therapy (CRT) and clinical outcomes. At least one-third of all patients treated with CRT fail to derive benefit. Patients without left bundle branch block (LBBB) or patients with smaller QRS duration (QRSd) respond less or not at all to CRT. We retrospectively assessed baseline characteristics, clinical and echocardiographic response, and outcomes of all patients who received CRT at our institution between December 2003 and July 2007. Patients were stratified into 4 groups according to their baseline QRS morphology and QRSd. A total of 496 patients were included in the study; 216 (43.5%) had LBBB and a QRSd ≥150 ms, 85 (17.1%) had LBBB and QRSd <150 ms, 92 (18.5%) had non-LBBB and a QRSd ≥150 ms, and 103 (20.8%) had non-LBBB and QRSd <150 ms. Echocardiographic response (change in ejection fraction) was better in patients with LBBB and QRSd ≥150 ms (12 ± 12%) than in those with LBBB and QRSd <150 ms (8 ± 10%), non-LBBB and QRSd ≥150 ms (5 ± 9%), and non-LBBB and QRSd <150 ms (3 ± 11%) (p < 0.0001). In a multivariate stepwise model with change in ejection fraction as the dependent variable, the presented classification was the most important independent variable (p = 0.0003). Long-term survival was better in LBBB patients with QRSd ≥150 ms (p = 0.02), but this difference was not significant after adjustment for other baseline characteristics (p = 0.15). QRS morphology is a more important baseline electrocardiographic determinant of CRT response than QRSd.